The Classification of Latin American Governments by the United States - Petras, James (Pontifícia Universidade Católica de São Paulo, 2004)
This article examines the classification of Latin American governments by the UnitedStates according to the criteria of willingness to implement the neoliberal agenda andcapacity to obtain popular legitimacy for this policy.